Workplace bullying in surgical environments in Saudi Arabia: A multiregional cross-sectional study - Hussah M Albuainain; Mariam M Alqurashi; Humood A Alsadery; Turki A Alghamdi; Abdulrahman A Alghamdi; Riyadh A Alghamdi; Talal A Albaqami; Saad M Alghamdi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Workplace bullying (WPB) is any sort of repeated and unjustified verbal, sexual, or physical intimidation that a person is exposed to by a group or another person in the workplace. In healthcare environments, practitioners are occasionally victims of WPB incidents. Bullying in surgical environments is an important issue that needs attention as it could affect patient care either directly or indirectly. The objective of this study was to assess the prevalence of bullying in surgical environments in multiple regions in Saudi Arabia. MATERIALS AND METHODS: This cross-sectional study was conducted among surgeons, trainees, interns, nurses, and students in surgical specialties in multiple Saudi regions. The survey was designed by Survey Monkey and posted online. The data were analyzed through SPSS Version-21 by computing descriptive statistics as frequency and percentages with graph construction. RESULTS: About two-thirds (65.2%) of the 788 study participants were male and were between the age of 20 and 29 years (67.8%). Consultants came first as perpetrators of bullying in the past 12 months (44.3%) and residents and interns were the major victims. The NAQ-R score ranged from 22.00 to 110.00, with a mean score of 42.47 (SD=17.9). Statistically significant association was found between mean NAQ-R score and age (P = 0.007), specialty (P = 0.002), and position (P < 0.001). CONCLUSION: WPB is a pervasive problem in surgical environments in multiple regions of Saudi Arabia. Consultants and specialists are the primary offenders in bullying, which makes the hospital an environment for bullying behaviors.